Application of random amplified polymorphic DNA (RAPD) analysis and plasmid profiles to the differentiation of Vibrio parahaemolyticus isolated from coastal waters - Son, Radu; Yuherman, Y; Rusul, G; Jamal, Khair; Samuel, L; Nasreldin, E.H.; Siti, M.A.W (1998)
Plasmid profiles and random amplified polymorphic DNA (RAPD) techniques were used to analyse the genetic differentiation of 57 isolates of Vibrio parahaemolyticus isolated from coastal water. Among the isolates, 16 plasmid patterns were observed, with plasmid sizes ranging from 1.5 to 7.6 megadalton. The two primers (Gen1-50-01, 5'-GTGCAATGAG-3' and Gen1-50-02, 5'-CAATGCGTCT-3') generated reproducible profiles of genomic DNA fingerprints producing bands ranging from 0.25 to 5.0 kb. The RAPD types profiles revealed a high level of DNA sequence diversity within the Vibrio parahaemolyticus isolates tested, as 48 RAPD types were observed for each primer respectively. Hence, plasmid profiles and RAPD-PCR analysis proved useful in discriminating the isolates. The later method proved to be more sensitive. Our data show that Vibrio parahaemolyticus isolates can be divided into at least 56 epidemiological subgroups on the basis of the plasmid profiles and RAPD-PCR results.